Occurrence of infection by Platynosomum illiciens (Braun, 1901) in captive neotropical primates - Silva, Klena S. M.; Silva, Reinaldo J. [UNESP]; Pereira, Washington L. A. (Springer Tokyo, 2012)
Platynosomum illiciens (Trematoda, Plagiorchida) is a trematode parasite reported in felids and falconiforms. It was identified in the gall bladder of eight captive neotropical necropsied primates from the National Primate Center (CENP), Ananindeua, State of Para, Brazil. This is the first description of Platynosomum illiciens as a parasite of primates.
Keywords: Neotropical primates; Platynosomum illiciens; Trematoda; Captivity